RESULTS OF ORIGINAL HERBAL MEDICINAL PRODUCT USE IN COMBINATION THERAPY OF PYELONEPHRITIS IN CHILDREN - M.V. Nezhdanova; E.V. Volgaeva; O.V. Galchina (Вопросы современной педиатрии)
The article considers pyelonephritis therapy in children. Authors have demonstrated in a controlled clinical study that combination therapy of antibiotic and herbal medicinal product Canephron N promoted normalization of leukocyte count, protein and malonic dialdehyde urine levels as well as interleukine 8 and tumor necrotizing factor serum concentrations.Key words: children, pyelonephritis, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(3):113-116)